Transcendental Epistemology Study of Philosophy of Wisdom Muta'aliyah Mulla Sadra - Fauziah Nurdin; Hasymsyah Nasution; Hasan Bakti Nasution (Budapest International Research and Critics University, 2019)
The aim of the study is to find out Transcendental Epistemology by using Muta'aliyah Mulla Sadra. This study used qualitative research methodology. The result of the study is Mullâ Shadrâ system is different from the emphasis on specific aspects of